2022
DOI: 10.48165/ijvsbt.18.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antibiotic Susceptibility of Avian Pathogenic Escherichia coli by Phenotypic and Genotypic Methods

Abstract: tEscherichia coli infection is one of the most important infections, which causes heavy economic losses in the poultry industry. It is caused by avian pathogenic E.coli (APEC), which belongs to the group Extra-intestinal Pathogenic E. coli (ExPEC). In this study, a total of 60 APEC isolates from various poultry farms located in and around Anand were evaluated for antibiotics susceptibility by disc diffusion (phenotypic) method for 21 different antibiotics. The E. coli isolates showed 100% resistance against pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 12 publications
2
7
5
Order By: Relevance
“…We found that 31% of the APEC isolates had phenotypic antibiotic resistance to GEN, which is less than the resistance rates of 76.4% reported in Nepal by Bista et al . [ 41 ], 76.7% in India [ 49 ], 57.2% in Jordan [ 50 ], 43.8% in Egypt [ 47 ], and 68.2% in China [ 48 ]; however, a similar resistance rate 32.5% was reported by Sankhi et al . [ 44 ] from Nepal.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…We found that 31% of the APEC isolates had phenotypic antibiotic resistance to GEN, which is less than the resistance rates of 76.4% reported in Nepal by Bista et al . [ 41 ], 76.7% in India [ 49 ], 57.2% in Jordan [ 50 ], 43.8% in Egypt [ 47 ], and 68.2% in China [ 48 ]; however, a similar resistance rate 32.5% was reported by Sankhi et al . [ 44 ] from Nepal.…”
Section: Discussionmentioning
confidence: 56%
“…[ 41 ] and Limbachiya et al . [ 49 ], respectively, both surpassing the lower resistance rates 16.6%–18.1% reported [ 48 , 52 ].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations